THE ROLE OF AI-SUPPORTED ACCOUNTING INFORMATION SYSTEMS IN ENHANCING THE APPLICATION OF REAL-TIME FINANCIAL REPORTING: AN APPLIED STUDY ON A SAMPLE OF BANKS LISTED IN THE IRAQ STOCK EXCHANGE - Abbas Hadi Abbood; Batool Hadi Mohammed; Ahmed Kadhim Sendw (Scholar Express Journals, 2025)
This research aiming to analyze the role of accounting information systems backed by (AI) technologies in improving the efficiency and correctness of real-time financial coverage in a sample of banks listed on the Iraq Stock Trade. The quality of financial and managerial decisions is improved and transparency is increased by preparing real-time financial reports, especially in a banking environment characterized by rapid changes and increasing competition. To collect data from multiple accounting and information technology employees in the targeted banks, the study utilized a descriptive-analytical approach and a field questionnaire. Using artificial intelligence-supported accounting information systems has a statistically significant positive relationship with the effectiveness and accuracy of real-time financial reporting, as shown in the analysis results. The study also demonstrated that AI technologies, such as machine learning, big data processing, and automation of accounting processes, effectively contribute to reducing the time required to prepare reports and improving the reliability and quality of the provided accounting information. The research recommends expanding the scope of AI utilization in accounting systems, developing digital infrastructure, and focusing on training banking human resources to keep pace with modern technological developments, thereby contributing to achieving the objectives of real-time financial reporting and enhancing the financial performance efficiency of banks.
Keywords: Accounting Information Systems; Artificial Intelligence; Real-Time Financial Reporting